Multipurpose cellulases of Promicromonospora sp. VP111, with broad substrate specificity and tolerance properties - Thomas, Lebin; Ram, Hari; Singh, Ved P. (Journal of Basic Microbiology, 2023)
Cellulolytic actinobacterium, Promicromonospora sp. VP111 concomitantly produced cellulases (CELs), xylanase and pectinase when grown on commercial cellulose and untreated agricultural lignocellulosic residues (wheat straw and sugarcane bagasse). Secreted CELs hydrolyzed (enhanced with Co2+ ion) multiple cellulosic substrates, including sodium carboxymethyl cellulose (Na-CMC), Whatman filter paper no. 1, microcrystalline cellulose (avicel), p-nitrophenyl-beta-D-glucopyranoside (pNPG), laminarin, and cellulose powder. The CELs showed stabilities in the presence of various chemicals, including glucose (0.2 M), detergents (1%, w/v or v/v), denaturants (1%, w/v or v/v), and sodium chloride (NaCl, 30%, w/v). The CELs were fractionated using ammonium sulfate precipitation and dialysis. Activities (%) of fractionated CELs were retained at 60 degrees C for endoglucanase/carboxymethyl cellulase (CMCase) (88.38), filter paper cellulase (FPase) (77.55), and beta-glucosidase (90.52), which indicated of thermo-stability. Similarly, the activities (%) for CMCase (85.79), FPase (82.48), and beta-glucosidase (85.92) at pH 8.5 indicated of alkaline-stability. Kinetic factors, K-m and V-max for endoglucanase component of fractionated CELs were 0.014 g/l and 158.23 mu M glucose/min/mL, respectively. Fractionated CELs yielded activation energies (kJ/mol) of 17.933, 6.294, and 4.207 for CMCase, FPase, and beta-glucosidase activities, respectively in linear thermostable Arrhenius plots. Thus, this study reports on the multipurpose CELs from an untreated agricultural residue utilizing Promicromonospora in relation to broad substrate specificity, halo-tolerance, alkaline-tolerance, detergent-tolerance, thermo-tolerance, organic solvent-tolerance, and end product-tolerance.
Keywords: cellulases; cellulose; Endoglucanase; Lignocellulose; Promicromonospora sp; VP111